Faktor-Faktor Yang Mempengaruhi Pertumbuhan Ekonomi Di Indonesia - Latunil Isman, Tania; Sentosa, Sri Ulfa (Universitas Negeri Padang, 2025)
This study aims to examine the influence of ICT services exports, foreign investment, inflation and labor force participation rate on Indonesia's economic growth. This type of research is quantitative research using secondary data. specifically the World Bank's time series data from 1993 to 2023. Multiple linear regression analysis is the analysis method used in this study. The results of this study indicate that all independent variables together have a significant effect on economic growth as the dependent variable. Partially, ICT services exports has a negative and insignificant effect on economic growth. Foreign investment have a positive and significant effect on economic growth, inflation has a negative and significant effect on economic growth. and labor force participation rate has a positive and insignificant effect on economic growth.